2001
DOI: 10.1186/cc1043
|View full text |Cite
|
Sign up to set email alerts
|

Plasma colloid osmotic pressure in healthy infants

Abstract: IntroductionPlasma COP is generated by the plasma proteins, particularly albumin, and is known to vary during various neonatal diseases [1][2][3][4]. Lower plasma COP favors a fluid shift from intravascular space into interstitial space, with subsequent formation of peripheral and pulmonary edema [3][4][5][6][7][8]. To stabilize the intravascular volume and prevent or reverse the events leading to peripheral and pulmonary edema, albumin or other colloid solutions are frequently administered, to maintain the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…1 a). For the infants from the control group with WG = 30 this pressure reached the value of = 2.5 kPa (19 mmHg), which is close to the mean value of blood colloid osmotic pressure of 23 mmHg measured for healthy infants one month old 24 . The shear stress (Fig.…”
Section: Resultssupporting
confidence: 81%
“…1 a). For the infants from the control group with WG = 30 this pressure reached the value of = 2.5 kPa (19 mmHg), which is close to the mean value of blood colloid osmotic pressure of 23 mmHg measured for healthy infants one month old 24 . The shear stress (Fig.…”
Section: Resultssupporting
confidence: 81%
“…COP p in healthy full-term (19.4 ± 2.2 mmHg) [ 23 ] and pre-term (15.4 ± 1.3 mmHg) [ 24 ] babies have been reported to be significantly lower than in healthy infants from 1 to 9 months of age [ 6 ], who may have values almost identical to that of adults (25 mmHg) [ 21 ]. Due to lack of data on changes in COP in infants up to 2 post-natal months, we anticipate a sharp increase in COP to occur within the first months of life.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of interstitial colloid osmotic pressure (COP i ), this is likely due to lack of generally accepted methods for isolating IF. What is clear, however, is that plasma colloid osmotic pressure (COP p ) increases during the first months after birth, reaching at one year of age, values comparable to those reported in adult subjects [ 6 ]. Furthermore, decreased COP p in disease states, like congenital analbuminemia and during surgery for congenital cardiac malformations, is associated with compromised pulmonary function and tissue edema [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sick neonates, regardless of maturity, have an even more decreased COP p [ 15 , 24 , 25 ]. Sussmane et al showed that COP p in healthy infants from 1 to 11 months is in proportion to adult values, with an anticipated COP p increase during the first month of life [ 26 ]. Throughout TH treatment in the present study, the mean COP p (14.3 ± 2.6 mmHg) coincides with earlier observations of lowered plasma COP in sick newborns [ 15 ].…”
Section: Discussionmentioning
confidence: 99%